Surgical Management of Posterior Cruciate Ligament Avulsion Fracture: A Case Report - Sadiwidayat, Komang Septian; Febyan; Dimitri, Dominicus (Indonesian Journal of Medicine, 2024)
Background: Posterior Cruciate Ligament (PCL) avulsion fractures are relatively rare but significant injuries to the knee. The diagnosis and management of these injuries can be complex and require a comprehensive approach Case Presentation: A 24-year-old female presented to the emergency department following a motorbike fall. She experienced significant pain in her knee and had a swollen popliteal fossa. Imaging studies, including X-ray and CT scan, revealed an avulsion fracture at the PCL insertion. The patient underwent successful surgical fixation of the avulsed fragment, following a positive posterior drawer, sag, and dial test suggesting an isolated PCL avulsion. Conclusion: This case underscores the importance of a comprehensive and individualized approach to the management of PCL avulsion fractures. It further emphasizes the need for future research to delineate the long-term outcomes of different treatment strategies and to develop evidence-based guidelines for this unique and challenging injury. Keywords: posterior cruciate ligament, avulsion fracture, knee injury, surgical fixation.